Pengaruh Profitabilitas dan Leverage Terhadap Audit Report Lag Pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Wulan Agistiani, Putri; Citra Mulyandani, Vina (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Audit report lag occurs when a company is late in submitting audited financial reports, which is the time required to complete the audited financial statements. Such delays can indicate problems with a company's financial statements, impacting decision-making for company owners and investors. This study aims to determine how profitability and leverage affect audit report lag. The sample comprises property & real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Using purposive sampling, 68 companies were selected as samples. The study employs quantitative methods, utilizing secondary data from financial and annual reports published on the IDX website (www.idx.co.id). Panel data regression analysis is conducted using the Eviews 12 application. The research findings indicate that profitability has a significant negative effect on audit report lag, leverage has no effect, and simultaneously, profitability and leverage have a positive effect on audit report lag.